Effects of different types of surfactants on AC breakdown voltage of refined, bleached and deodorized palm oil based CuO nanofluids - Mohamad N.A.; Azis N.; Jasni J.; Yunus R.; Ab Kadir M.Z.A.; Yaakub Z. (IEEE Computer Society, 2023)
Bleaching; Cationic surfactants; Cleaning; Copper oxides; Dyes; Electric breakdown; Nanofluidics; Oleic acid; Palm oil; Petroleum refining; Sulfur compounds; AC breakdowns; Cetyl trimethyl ammonium bromides; Cetyltrimethylammonium bromide; Cuo nanofluids; Gap distances; Oil based; Refined; Volume percentage; Sodium dodecyl sulfate